2012
DOI: 10.1016/j.cyto.2012.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Association between pro- and anti-inflammatory cytokine genes and a symptom cluster of pain, fatigue, sleep disturbance, and depression

Abstract: Because multiple symptoms associated with “sickness behavior” have a negative impact on functional status and quality of life, increased information on the mechanisms that underlie inter-individual variability in this symptom experience is needed. The purposes of this study were to determine: if distinct classes of individuals could be identified based on their experience with pain, fatigue, sleep disturbance, and depression; if these classes differed on demographic and clinical characteristics; and if variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
165
3
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(192 citation statements)
references
References 87 publications
21
165
3
3
Order By: Relevance
“…Although symptoms experienced generally depend on treatment, primary tumour site or other co-morbid conditions, certain symptoms may be more closely related Muthukkumaran Thiagarajan 1 , Caryn Mei Hsien Chan 2 *, Ho Gwo Fuang 1 , Tan Seng Beng 2 , MA Atiliyana 1 , NA Yahaya 3 to psychological reasons (Cleeland, 2007). Multiple symptoms may also occur as a cluster (Illi, Miaskowski, Cooper et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although symptoms experienced generally depend on treatment, primary tumour site or other co-morbid conditions, certain symptoms may be more closely related Muthukkumaran Thiagarajan 1 , Caryn Mei Hsien Chan 2 *, Ho Gwo Fuang 1 , Tan Seng Beng 2 , MA Atiliyana 1 , NA Yahaya 3 to psychological reasons (Cleeland, 2007). Multiple symptoms may also occur as a cluster (Illi, Miaskowski, Cooper et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In all 13 studies, subgroups of patients who reported a low and high number of symptoms were found. In the studies that reported three [7,8,10,12,14,15], four [5,6,11], or five [13] subgroups, the distinguishing characteristics of the subgroups of patients with moderate symptoms were highly variable in terms of the number and types of symptoms, as well as in the specific demographic and clinical characteristics that distinguished among these subgroups.…”
mentioning
confidence: 99%
“…To date, 13 studies were found that used a variety of analytic approaches to classify oncology patients based on their symptom experience [3][4][5][6][7][8][9][10][11][12][13][14][15]. Across these studies, two [3,4,9] to five [13] groups of patients were identified.…”
mentioning
confidence: 99%
See 2 more Smart Citations